Assessing the effects of changes in care commissioning guidelines at a tertiary centre in London on the provision of NHS-funded procedures of limited clinical effectiveness: an 11-year retrospective database analysis. Issue 7 (28th July 2017) - Rahman, Shafiq; Langridge, Benjamin; Hachach-Haram, Nadine; Hansen, Esther; Bootle, Anna; Bystrzonowski, Nicola; Hamilton, Stephen; Mosahebi, Afshin
Abstract : Objectives: The main objective of this study was to assess the impact of changes in care commissioning policies on National Health Service (NHS)-funded cosmetic procedures over an 11-year period at our centre. Setting: The setting was a tertiary care hospital in London regulated by the North Central London Hospitals NHS Trust care commissioning group. Participants: We included all patients logged on to our database at the time of the study which was 2087 but later excluded 61 from analysis due to insufficient information. Primary and secondary outcome measures: The main outcome measures were the results of tribunal assessment for different cosmetic surgeries which were either accepted, rejected or inconclusive based on the panel meeting. Results: There were a total of 2087 patient requests considered between 2004 and 2015, of which 715 (34%) were accepted, 1311 (63%) were declined and 61 (3%) had inconclusive results. The implementation of local care commissioning guidelines has reduced access to cosmetic surgeries. Within this period, the proportion of procedures accepted has fallen from 36% in 2004 to 21% in 2015 (χ 2 ; p<0.05, 95% CI). Conclusion: Local guidance on procedures of limited clinical effectiveness is a useful, although not evidence-based selection process to reduce access to cosmetic surgery in line with increasing financial constraints. However, patients with a physical impairment may not receive treatment in comparison to previous years, and this can have a negative impact on their quality of life.